An Analysis of Sentence Effectiveness in Thesis Abstracts of Undergraduate Nursing Students - I Putu Gede Sutrisna; Ida Bagus Putrayasa; I Nengah Suandi (Global Action and Education for Society, 2025)
Writing effective sentences is essential in academic writing, particularly in abstract sections which serve as the initial summary of a research work. This study aims to analyze the effectiveness of sentences used in abstracts of undergraduate nursing students’ theses at ITEKES Bali. Using a descriptive qualitative approach, the data consisted of 30 thesis abstracts from the 2024 academic year, selected through purposive sampling. The analysis was based on five criteria of effective sentences according to Ramlan (2005): unity, coherence, conciseness, accuracy, and logical structure. The results showed that out of 428 analyzed sentences, only 221 (51.6%) were considered effective, while 207 (48.4%) were ineffective. The most frequent issues were lack of coherence (28.5%), verbosity (21.7%), and weak sentence unity (18.4%). These findings indicate a significant gap between the expected academic writing standards and students' linguistic abilities. It also suggests a need for reinforced instruction on scientific writing and sentence construction in the academic curriculum. This research contributes to the development of targeted language teaching strategies to enhance the academic literacy of nursing students in higher education settings.